HspB1, HspB5 and HspB4 in Human Cancers: Potent Oncogenic Role of Some of Their Client Proteins - Arrigo, André-Patrick (MDPI, 2014)
Human small heat shock proteins are molecular chaperones that regulate fundamental cellular processes in normal unstressed cells as well as in many cancer cells where they are over-expressed. These proteins are characterized by cell physiology dependent changes in their oligomerization and phosphorylation status. These structural changes allow them to interact with many different client proteins that subsequently display modified activity and/or half-life. Nowdays, the protein interactomes of small Hsps are under intense investigations and will represent, when completed, key parameters to elaborate therapeutic strategies aimed at modulating the functions of these chaperones. Here, we have analyzed the potential pro-cancerous roles of several client proteins that have been described so far to interact with HspB1 (Hsp27) and its close members HspB5 (αB-crystallin) and HspB4 (αA-crystallin).